2017
DOI: 10.1371/currents.md.8a7e35c50fa2b48156799d3c39788175
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A Virus Infection Damages Zebrafish Skeletal Muscle and Exacerbates Disease in Zebrafish Modeling Duchenne Muscular Dystrophy

Abstract: INTRODUCTION: Both genetic and infectious diseases can result in skeletal muscle degeneration, inflammation, pain, and/or weakness. Duchenne muscular dystrophy (DMD) is the most common congenital muscle disease. DMD causes progressive muscle wasting due to mutations in Dystrophin. Influenza A and B viruses are frequently associated with muscle complications, especially in children. Infections activate an immune response and immunosuppressant drugs reduce DMD symptoms. These data suggest that the immune system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Tg(NF-kB:EGFP) zebrafish were continuously exposed to 0 or 2% EtOH from 30 hpf on and then fixed at 3 dpf. Muscle fibers in control Tg(NF-kB:EGFP) zebrafish were long and linear ( Figure 3 A1,A2) and did not express GFP at 72 hpf ( Figure 3 A3–A6, [ 25 ]). EtOH treatment increased NF-kB activity as evidenced by increased GFP expression in muscle fibers ( Figure 3 B3–B6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tg(NF-kB:EGFP) zebrafish were continuously exposed to 0 or 2% EtOH from 30 hpf on and then fixed at 3 dpf. Muscle fibers in control Tg(NF-kB:EGFP) zebrafish were long and linear ( Figure 3 A1,A2) and did not express GFP at 72 hpf ( Figure 3 A3–A6, [ 25 ]). EtOH treatment increased NF-kB activity as evidenced by increased GFP expression in muscle fibers ( Figure 3 B3–B6).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the primary cause of muscle damage in laminin a2 mutant zebrafish is failure of adhesion of muscle fibers to the MTJ. We found that human influenza A virus causes both sarcolemmal damage and disrupts muscle fiber adhesion to the MTJ [ 25 ], indicating that these modes of damage are not mutually exclusive.…”
Section: Introductionmentioning
confidence: 99%
“…2 dpf zebrafish were infected with PR8 and muscle fiber damage was observed [244]. Muscle damage seemed to worsen at 48 hpi compared to 24 hpi.…”
Section: Zebrafishmentioning
confidence: 99%
“…This effect could be due to pro-inflammatory innate immune signaling cascades being induced via the NFkB pathway (suggested by using NFkB reporter line (NFkB:EGFP) nc ). Using a transgenic fish, Tg(BACmpo:gfp) i114 where GFP expression was controlled by the neutrophil-specific myeloperoxidase (mpo) promoter, it was reported that neutrophils infiltrated muscle tissue and was localized to the unanchored end of retracted fibers after infection [244]. This could be mediated by the p38 MAPK, Rho/ROCK and PKC pathways [244].…”
Section: Zebrafishmentioning
confidence: 99%
See 1 more Smart Citation